HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU KONSUMSI IKAN DI KECAMATAN DANAU SIPIN KOTA JAMBI - Asmaida Asmaida; Zikri Sulaiman (Jurnal MeA (Media Agribisnis), 2020)
Communities of  “Danau sipin” District in  Jambi City especially housewives were mostly showed various ethnic groups with a different levels of education and have  an autonomy decision in determining their food consumption, especially fish. This study aimed to describe the characteristics, the level of knowledge, attitudes and behavior of housewives toward to the fish consumption, and also to analyze the relationship between both  knowledge and attitudes toward to fish consumption behavior. The Age of housewives ranging from 27 – 55 years with an average age of 38.18 years. The lowest last education level is the SLTP and the highest educated SI, with a majority educated SLTA (38.64%). The type of work is housewives, ASN, entrepreneurial, private employees and honorers, with a majority as housewives (38.64%). The number of family members ranges from 3 to 6 people with an average of 4 people. The results showed that the level of knowledge of housewives gave  75%. as high category while the attitude of fish consumtion  was showed an encouraged category  as 86.36%. Fish consumption behavior showed a good category of 54.54%. There was no relationship between the knowledge and fish consumption behavior. The same case there was also showed  no relationship between attitude and fish consumption behavior. Keywords: Relationships, Knowledge, Attitudes, Fish.